Fabrication of micrometre-sized periodic gratings in free-standing metallic foils for laser–plasma experiments. (10th December 2022) - Gheorghiu, C. C.; Cerchez, M.; Aktan, E.; Prasad, R.; Yilmaz, F.; Yilmaz, N.; Popa, D.; Willi, O.; Leca, V.
Abstract: Engineered targets are expected to play a key role in future high-power laser experiments calling for joined, extensive knowledge in materials properties, engineering techniques and plasma physics. In this work, we propose a novel patterning procedure of self-supported 10 μm thick Au and Cu foils for obtaining micrometre-sized periodic gratings as targets for high-power laser applications. Accessible techniques were considered, by using cold rolling, electron-beam lithography and the Ar-ion milling process. The developed patterning procedure allows efficient control of the grating and foil surface on large area. Targets consisting of patterned regions of 450 μm × 450 μm, with 2 μm periodic gratings, were prepared on 25 mm × 25 mm Au and Cu free-standing foils, and preliminary investigations of the micro-targets interacting with an ultrashort, relativistic laser pulse were performed. These test experiments demonstrated that, in certain conditions, the micro-gratings show enhanced laser energy absorption and higher efficiency in accelerating charge particle beams compared with planar thin foils of similar thickness.